Counter Narrative Policy to Handling Radicalism in Indonesia - Khaerul Umam; Reni Qurroti Aeni; Feni Astuti (UIN Sunan Gunung Djati, 2022)
Contra-radicalization was designed to counter radical ideology, primarily transnational ideology in Indonesia. In its realization, it has two approaches, soft and hard, with two methods, online and offline. However, based on the fact that those radical ideologies are still present virtually and in reality. Thus, this research aims to describe how the program is run by BNPT (National Counter Terrorism Agency) using its strategy, method, and approaches. This research used Grindle’s implementation theory of policy content, with the method used being descriptive and qualitative. The results showed that there are indicators challenging the implementation of the program such as the clarity of Interest affected, lack of resources used, and the characteristic of the regime.